Semiconductive microporous hydrogen-bonded organophosphonic acid frameworks - Tholen, Patrik; Peeples, Craig A.; Schaper, Raoul; Bayraktar, Ceyda; Erkal, Turan Selman; Ayhan, Mehmet Menaf; Cosut, Bunyemin (Nature Publishing Group, 2020)
Herein, we report a semiconductive, proton-conductive, microporous hydrogen-bonded organic framework (HOF) derived from phenylphosphonic acid and 5,10,15,20-tetrakis[p-phenylphosphonic acid] porphyrin (GTUB5). The structure of GTUB5 was characterized using single crystal X-ray diffraction. A narrow band gap of 1.56eV was extracted from a UV-Vis spectrum of pure GTUB5 crystals, in excellent agreement with the 1.65eV band gap obtained from DFT calculations. The same band gap was also measured for GTUB5 in DMSO. The proton conductivity of GTUB5 was measured to be 3.00x10(-6)Scm(-1) at 75 degrees C and 75% relative humidity. The surface area was estimated to be 422m(2)g(-1) from grand canonical Monte Carlo simulations. XRD showed that GTUB5 is thermally stable under relative humidities of up to 90% at 90 degrees C. These findings pave the way for a new family of organic, microporous, and semiconducting materials with high surface areas and high thermal stabilities. Research in hydrogen-bonded organic frameworks (HOFs) has gained interest in recent years due to their facile design and synthesis but no semiconducting HOF has been reported to date. Here the authors report a thermally stable and proton-conductive organic semiconductor based on a porphyrin HOF.
Keywords: Metal-Organic Frameworks; Proton Conduction; Adsorption; Mofs; Gas; Crystalline; Perspective; Chemistry; Zirconium